2017
DOI: 10.1002/cbdv.201700083
|View full text |Cite
|
Sign up to set email alerts
|

Melanogenesis‐Inhibitory and Antioxidant Activities of Phenolics from Periploca forrestii

Abstract: Two new tetrahydrofuran-type lignans, (-)-gentioluteol 9-O-β-d-glucopyranoside (1), (-)-berchemol 9-O-β-d-apiofuranosyl-(1→6)-O-β-d-glucopyranoside (2), along with sixteen known compounds 3 - 18 were isolated from the 95% EtOH extract of the stems of Periploca forrestii. The structures of the new tetrahydrofuran-type lignans were determined by HR-ESI-MS and various NMR techniques in combination with CD method. Then, their antioxidant abilities were evaluated by 1,1-diphenyl-2-picrylhydrazyl (DPPH), 2,2'-azinob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Furthermore, we have evaluated the crude extracts and isolated compounds for their oxidation resistance ability as well as melanogenesis inhibitory activity, which is considered to be related with the former . In addition, we also choose compound 8 to evaluate the inhibitory activity of tyrosinase which plays an important role in regulating melanin formation …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we have evaluated the crude extracts and isolated compounds for their oxidation resistance ability as well as melanogenesis inhibitory activity, which is considered to be related with the former . In addition, we also choose compound 8 to evaluate the inhibitory activity of tyrosinase which plays an important role in regulating melanin formation …”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, compounds 1 – 7 also displayed high scavenging effect in the range of 0.87 – 8.43 μ m Trolox /μ m by ABTS assay, as well as exhibited moderate – higher ferric reducing power in the range of 1.01 – 5.79 μ m Fe 2+ /μ m by FRAP assay. It was the similar trend on DPPH and ABTS assays, which is due to compounds 1 – 7 possess the multiple phenolic OH groups leading to increase of the H‐radical‐donating activity . In addition, in the structure–activity relationship research of these compounds, it illustrated that compounds 3 and 4 showed more potent antioxidant activities than other compounds, because more phenolic OH groups can increased the antioxidant activities.…”
Section: Resultsmentioning
confidence: 56%
“…Melanogenesis‐inhibition assay in the α ‐MSH‐stimulated B16 melanoma cells was performed as described previously …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several in vivo and in vitro studies of P. forrestii or P. forrestii-containing Chinese medicine have also focused on delineating their effects on antiarthritis activities [ 24 26 ]. In addition, P. forrestii also exert an anti-inflammatory effect, antiallergy activities, and antioxidant activities [ 27 29 ].…”
Section: Introductionmentioning
confidence: 99%